A bivalent vaccine comprised of inactivated Aeromonas veronii and Edwardsiella ictaluri stimulates protective immune responses in yellow‐head catfish, Pelteobagrus fulvidraco. (11th July 2021) - Zeng, Jia; Ouyang, AoTian; Wang, Huabing; Liu, Wenzhi; Xue, Mingyang; Zhou, Yong; Ai, Taoshan; Zeng, Lingbing; Liu, Xiaoling
Abstract: Yellow‐head catfish, Pelteobagrus fulvidraco, is an economically important specific species in aquaculture in China. However, at present disease has become a major concern of this fish. In this study, a bivalent vaccine was generated, containing two formalin‐inactivated bacteria at different mixing ratio of 3:7, 5:5 and 7:3 of A . veronii and E . ictaluri in volume with a concentration at 1.0 × 10 8 CFU mL −1 for each.The immunization efficacies were evaluated by measuring lysozyme activity, serum total protein, serum C3, specific antibodies, expression of immune‐related genes and survival rate against A . veronii or E . ictaluri . The results showed that the bivalent vaccine with a mixing ratio of 3:7 of A . veronii and E . ictaluri in volume presented the highest immunization efficacy. In this immunization group, the lysozyme activity, serum total protein and serum C3 had a noticeable increase at 7 dpi. IgM gene was significantly up‐regulated to the peak at 7 dpi in the spleen and at 14 dpi in the kidney after immunization. MR (Mannose receptor) and Ctl (C‐type lectin) genes significantly increased and reached their maximum at 24 h after immunization in both spleen and head kidney. Higher antibody levels were observed in vaccinated fish at day 21 post immunization. The challenge test showed that the relative survival percent in the immunized group with the mixing ratio of 3:7 of A . veronii and E . ictaluri in volume was 50.61% ± 2.64 and 62.82% ± 2.22 against A . veronii and E . ictaluri infection respectively. These results indicated that the bivalent vaccine of inactivated A . veronii and E . ictaluri can effectively induce immune responses and protect yellow‐head catfish against A . veronii and E . ictaluri infection.